Proceso de ASC - ADMINISTRACION PUBLICA EN AMERICA LATINA: UN ESTADO DEL ARTE SOBRE LOS ESTUDIOS CONTEMPORANEOS 2018-2022 (2023)
This project analyzes the scientific production on public administration in Latin America found in three databases: Scopus, Web of Science and Dimensions, from 2012 to 2022, based on an exploratory-descriptive bibliometric approach with the aim of identifying the main theoretical innovations, debates, and trends in the field. The information gathering process was supported by the Luis Echavarría Villegas Cultural Center Library of the EAFIT University and was developed in three stages: definition of search parameters and criteria, selection of databases and systematization of the information.